Menstrual restriction prevalence and association with intimate partner violence among Nepali women. Issue 1 (28th September 2018) - Cardoso, Lauren F; Clark, Cari Jo; Rivers, Kelsey; Ferguson, Gemma; Shrestha, Binita; Gupta, Jhumka
Abstract : Introduction: Emerging research has linked women's sanitation and menstrual hygiene experiences with increased vulnerability to violence outside the home. Few studies, however, have investigated the relationship between menstruation and violence perpetrated by family members. This type of violence may be linked specifically to restrictions placed on women during menstruation, which are common in some regions of Nepal owing to shared power differentials that disfavour women, and societal norms that stigmatise menstruation. Objective: To record the prevalence of menstrual restrictions experienced by married women and examine potential associations between intimate partner violence (IPV) in the past year and menstrual restrictions imposed by husbands and/or in-laws among women in three districts of Nepal: Nawalparasi, Kapilvastu and Chitwan. Methods: Baseline data from a larger randomised control trial aiming to reduce IPV in three districts of the Terai region of Nepal (n=1800) were used to assess the prevalence of menstrual restrictions and the association with IPV. Results: Nearlythree out of four women (72.3%) reported experiencing high menstrual restriction, or two or more types of menstrual restriction. When controlling for demographic variables and IPV, no type of IPV was associated with high menstrual restrictions. Conclusion: The experience of menstrual restriction was widespread in this sample of women in Nepal. Future research should seek to identify how best to capture menstrual stigma and deviations around such norms. The global health and development community should prioritise integration with existing water and sanitation programmes to reduce stigma and ensure the well-being of menstruating women and girls. Trial registration number: NCT02942433 .